Efficiency of left and right handed clinicians using right-handed dental chairs and instruments in periodontal scaling treatment in UPCD - Capanzana, Kristine T.; Enriquez, Katriona Jay P.; Galban, Angelita B. (Adviser).
According to Mason in 2009, almost 20% of the population are left-handed and they struggle in a world designed for right-handed individuals. They adapt to equipment and instruments not fit for them, thus, sacrificing their physical and psychological health. People believed to have the same dilemma are left-handed dental clinicians. This study was done to evaluate the performance of left and right- handed clinicians using right-handed designed equipment and instruments in periodontal scaling and determine problems arising from the procedure. Methods: A cross-sectional study design was done where 14 dental clinicians, 7 left-handed and 7 right-handed participated in the study Data collection was divided into three parts: a questionnaire regarding operatory positions and problems encountered while treating patients, an actual scaling procedure on mild gingivitis cases, and an observer recording the over-all treatment process and treatment outcomes. Test for equality of variances using F-test was done for time spent during the procedure and amount of plaque remaining. After plotting the results of the said variables, t-test was used to interpret and compare the results Minitab ver15 was used to calculate statistical data. Results: Left-handed clinicians using right-handed dental find the cuspidor a hindrance and there is insufficient room for movement during dental procedures. Furthermore, they claims to have problems on the location of the bracket table and short tubes for the handpieces. Length of time of treatment and percentage of plaque removal was the same for the left and right-handed group. According to the observer, both groups exhibited deviation from the ideal operating positions, had ample of room for movement and move a lot around the chair in order to gain adequate access and visibility. Conclusion: Amount of time and percentage of deposit removal by the left-handed participants showed no statistical difference with that of the right-handed clinicians regardless of the dental chair unit. However, this is not an indication that everything else that is correlated to the performance of the simple dental procedure is ideal. There is still a lot to improve in terms of making the workplace ergonomic and encouraging the clinician to work following ergonomic principles.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.